2019
DOI: 10.2147/ppa.s217578
|View full text |Cite
|
Sign up to set email alerts
|

<p>Parental acceptance of the utilization of silver diamine fluoride on their child’s primary and permanent teeth [Corrigendum]</p>

Abstract: Parental acceptance of the utilization of silver diamine fluoride on their child's primary and permanent teeth [Corrigendum]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This is in sequence with what Clemens et al, Crystal et al, and Bagher et al have stated in the related literature. [15][16][17] The questionnaire was administered in both Spanish and English, either online or on paper, in the previous studies. [15,17] In our research, parents had been interviewed by a qualified dental professional who discussed all the benefits and drawbacks of using SDF.…”
Section: Discussionmentioning
confidence: 99%
“…This is in sequence with what Clemens et al, Crystal et al, and Bagher et al have stated in the related literature. [15][16][17] The questionnaire was administered in both Spanish and English, either online or on paper, in the previous studies. [15,17] In our research, parents had been interviewed by a qualified dental professional who discussed all the benefits and drawbacks of using SDF.…”
Section: Discussionmentioning
confidence: 99%
“…A KAP study also reported tooth discoloration (90.7%) and limited knowledge of the parents (58.3%) and their consent (64.8%) to be a major obstacle in the use of SDF 16 . Due to these reasons, the use of SDF in posterior teeth has shown better parental acceptance compared to its use in anterior teeth 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike SDF, its lack of staining and neutral flavor positions it to be used throughout the mouth, and particularly for permanent anterior teeth. 30 It is not used to seal in caries, and therefore may be more accepted by dentists than sealants. 30,31 For dental clinics, the profit margin for Curodont is superior, because it takes less clinician time to perform the application than to place restorative fillings.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…30 It is not used to seal in caries, and therefore may be more accepted by dentists than sealants. 30,31 For dental clinics, the profit margin for Curodont is superior, because it takes less clinician time to perform the application than to place restorative fillings.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%